Analisis Kesesuaian Lahan Untuk Tanam Padi Sawah dan Kedelai di Kecamatan Cawas Kabupaten Klaten - Apridayanti, Apridayanti; , Ir. Taryono, M.Si; , Drs. Suharjo, M.Si (2016)
This research entitled "Analysis of the Land Suitability for Crop Rice and Soybean in Cawas Klaten District", the purpose of the research to fine out the (1) land suitability paddy rice and soybeans in the research area; end (2) limiting factors that affect the land suitability for rice crop and soybean crops research areas. The method used in this research is a survey,while the method staratifid sampling and laboratory testing. Data collected consisted of: drainage, texture, depth evektif ground, KPK, P2O5, K20, pH Land, Ntotal, salinity, slope, surface rocks, rock outcrops, the number of dry months, the amount of average rainfall, flooding. The results showed: class land suitability for rice crops in the study consisted of two classes, namely S3 and S2 with drainage limiting factor, K20, flood; and class land suitability for soybean crops, namely, S2, S3, with the limiting factor drainage, K2O, P2O5, rock outcrops, flood. Keywords: land suitability, the limiting factor